Kompetensi Profesional Guru SMK Bidang Keahlian Teknik Bangunan di Medan - Zulkifli Matondang (Jurnal Pendidikan dan Kebudayaan, 2010)
This study aimed to know of teacher’s profesional competence at SMK (vocational scholl) in the field of building construction. Before to measure of teacher’s profesional competence, developing a standard instrument. The study was conducted in two phases: a rational try-out through experts’ assessment, followed by an empirical try-out. The first phase incorporated 20 experts; i.e. university lecturers of building construction. In the second phase, a competence test was administered to 276 teachers in Medan. Construct validity was examined by a factor analysis technique. The results indicated that the indicators fitted the construct; each indicator had a factor loading higher than 0.30. Varimax rotation resulted in a decrease in the factors of competence test, compared to the previously theorized, as profesional dimension had 10 factors. The reliability of the instrument was evaluated by KR-20 formula, and the coefficient 0.858 Therefore, it can be concluded that the instrument can be used to measure the competence of building construction teachers of SMK. The result study was teacher’s profesional competence at SMK in Medan repair to improved, therefore requar to add of teacher’s knowladge in their field. ABSTRAK Penelitian bertujuan untuk mengetahui kompetensi profesional guru SMK bidang keahliah teknik bangunan. Sebelum pengukuran kompetensi profesional guru, dikembangkan tes yang standar. Proses pengembangan tes dilakukan dengan dua fase yaitu melalui expert jugment oleh ahli dan ujicoba empiris. Pertama, dilibatkan 20 orang ahli yang terdiri dari: doktor evalusi, dosen teknik bangunan, dan guru. Kedua, ujicoba dilakukan pada 276 orang guru bidang keahliah teknik bangunan di Medan. Validitas konstruk tes dihitung dengan analisis faktor. Hasil penelitian menunjukkan bahwa faktor yang dibentuk oleh kompetensi profesional cukup baik. Setiap indikator memiliki loading faktor diatas 0.30. Dengan metode rotasi varimax diperoleh 10 faktor yang membentuk kompetensi profesinal guru SMK. Reliabiulitas tes dihitung dengan rumus KR-20, dan diperoleh koefisien reabilitas sebesar 0,858. Hasil perhitungan menyimpulkan bahwa tes yang dikembangkan dapat digunakan untuk mengukur kompetensi profesional guru SMK. Hasil pengukuran diperoleh kompetensi profesional guru SMK bidang keahliah teknik bangunan di Medan masuk pada kategori perlu perbaikan, sehingga perlu meningkatkan pengetahuan guru di bidangnya.